Pengaruh Tunjangan Kinerja, Budaya Organisasi dan Motivasi terhadap Kinerja Pegawai Biro Organisasi Sekertariat Daerah Provinsi Papua Barat - Angelia Intania Sihole; Giri Dwi Nanda; Asri; Nikolina Balia (Insan Cita Bongaya Research Journal, 2025)
This study aims to analyze the Influence of Performance Allowances, Organizational Culture and Motivation on Employee Performance. This research approach uses a quantitative approach of primary data through the distribution of questionnaires to 40 employees of the Regional Secretariat Organization Bureau of West Papua Province. To measure the direct influence of the variables of Performance Allowance, Organizational Culture and Work Motivation on Employee Performance with the help of an analysis tool using SPSS v.25. The results of the study show that partially the performance allowance variable has a positive and significant effect on employee performance, the organizational culture variable has a positive and significant effect on employee performance and the work motivation variable has a positive and significant effect on employee performance. Simultaneously, the variables of Performance Allowance, Organizational Culture and Work Motivation have a positive and significant effect on the Performance of Employees of the Regional Secretariat Organization Bureau of West Papua Province. From the results of the standardized Beta coefficients, it can be seen that the performance allowance variable is more dominant in influencing the performance of employees of the West Papua Provincial Secretariat Organization Bureau